Implementasi Algoritma Fp-Growth Pada Persediaan Barang Elektrikal - Wilson Gultom, Andre (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Asia Sinar Inti Abadi is a company that operates in the field of selling electrical components, various electrical components that are bought and sold, such as in panel assembly. To increase sales, management must organize the pattern or layout of components that are often in demand by buyers, resulting in large turnover. The problem that has occurred so far is that the pattern of component placement is irregular so that buyers are confused in choosing the electrical components needed. One of the solutions offered is to develop and improve the management of the layout of electrical goods at PT. Asia Sinar Inti Abadi uses the FP Growth algorithm, where each itemset can be identified so that sales that are frequently purchased by consumers can be placed in a section that is easy to see and easy to get. The results of implementing the FP Growth Algorithm using a desktop-based application can make it easier for management to decide on the layout of frequently used electrical goods, where frequently used components will be placed in parts that are easily seen by potential buyers. By using the FP Growth method, you can find out how much confidence each item set has along with the support value.